Multiphoton Microscopy of Oral Tissues: Review - Martínez-Ojeda, Rosa M.; Pérez-Cárceles, María D.; Ardelean, Lavinia C.; Stanciu, Stefan G.; Bueno, Juan M. (Frontiers in Physics, 2020)
Multiphoton microscopy (MPM) is currently acknowledged as a very powerful method for the visualization and analysis of tissues in biomedicine. It allows high resolution, deep optical sectioning and reduced photodamage. MPM does not require labeling and is deployable both in-vivo and ex-vivo, which simplifies the diagnostic procedure compared to traditional histology approaches based on tissue fixation and staining. Among the important applications of MPM in medicine, differentiation of healthy from pathological samples has gained massive interest over the past years, but MPM is also very useful for acquiring new insights on how various pathologies originate and progress. In this work we review the use of MPM in imaging assays focused on investigating unlabeled oral tissues (teeth and oral mucosa) and discuss a series of important results which hold potential for enabling a next generation of oral tissue characterization/diagnostic frameworks. The surveyed literature shows that nonlinear optical imaging tools can significantly contribute to achieve a better understanding of oral cavity tissues, by allowing the accurate analysis of morphological structures and relevant biochemical processes.